Protein S is a cofactor for platelet and endothelial tissue factor pathway inhibitor-a but not for cell surface-associated tissue factor pathway inhibitor - Wood, J.; Ellery, Paul; Maroney, S.; Mast, A. (2014)
OBJECTIVE - Tissue factor pathway inhibitor (TFPI) is produced in 2 isoforms: TFPIa, a soluble protein in plasma, platelets, and endothelial cells, and TFPIß, a glycosylphosphatidylinositol-anchored protein on endothelium. Protein S (PS) functions as a cofactor for TFPIa, enhancing the inhibition of factor Xa. However, PS does not alter the inhibition of prothrombinase by TFPIa, and PS interactions with TFPIß are undescribed. Thus, the physiological role and scope of the PS-TFPI system remain unclear. APPROACH AND RESULTS - Here, the cofactor activity of PS toward platelet and endothelial TFPIa and endothelial TFPIß was quantified. PS enhanced the inhibition of factor Xa by TFPIa from platelets and endothelial cells and stabilized the TFPIa/factor Xa inhibitory complex, delaying thrombin generation by prothrombinase. By contrast, PS did not enhance the inhibitory activity of TFPIß or a membrane-anchored form of TFPI containing the PS-binding third Kunitz domain (K1K2K3) although PS did function as a cofactor for K1K2K3 enzymatically released from the cell surface. CONCLUSIONS - The PS-TFPI anticoagulant system is limited to plasma TFPIa and TFPIa released from platelets and endothelial cells. PS likely functions to localize solution-phase TFPIa to the cell surface, where factor Xa is bound. PS does not alter the activity of membrane-associated TFPI. Because activated platelets release TFPIa and PS, the PS-TFPIa anticoagulant system may act physiologically to dampen thrombin generation at the platelet surface. © 2013 American Heart Association, Inc.